Multi-omics insight into the molecular networks of mental disorder related genetic pathways in the pathogenesis of inflammatory bowel disease - Meng Zhang; Jianhui Zhao; Haosen Ji; Yuqian Tan; Siyun Zhou; Jing Sun; Yuan Ding; Xue Li (Translational Psychiatry)
Abstract Mental disorders are associated with inflammatory bowel disease (IBD), but the genetic pathophysiology is not fully understood. We obtained data on mental disorder-related gene methylation, expression, protein levels, and summary statistics of IBD, and performed Summary data-based Mendelian randomization and colocalization analyses to explore the causal associations and shared causal genetic variants between multiple molecular traits and IBD. Integrating multi-omics data, we found QDPR, DBI and MAX are associated with ulcerative colitis (UC) risk, while HP is linked to IBD risk. Inverse associations between gene methylation (cg0880851 and cg26689483) and expression are observed in QDPR, consistent with their detrimental role in UC. Methylation of DBI (cg11066750) protects against UC by enhancing expression. Higher levels of DBI (OR = 0.79, 95%CI = 0.69–0.90) and MAX (OR = 0.74, 95%CI = 0.62–0.90) encoded proteins are inversely associated with UC risk, while higher QDPR (OR = 1.17, 95%CI = 1.07–1.28) and HP (OR = 1.09, 95%CI = 1.04–1.14) levels increase UC and IBD risk. Our findings advance the understanding of IBD’s pathogenic mechanisms and gut-brain interaction.